2012
DOI: 10.1097/ncn.0b013e31823eb73a
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Information Technology and Medical-Surgical Nurses

Abstract: Healthcare information technology in US hospitals and ambulatory care centers continues to expand, and nurses are expected to effectively and efficiently utilize this technology. Researchers suggest that clinical information systems have expanded the realm of nursing to integrate technology as an element as important in nursing practice as the patient or population being served. This study sought to explore how medical surgical nurses make use of healthcare information technology in their current clinical prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…9 Over the years, several studies and reviews have been conducted focusing on practitioners' acceptance and use. 2,4,6,10 One study showed that nurses were not overtly influenced by the use of information technology despite its potential to support their clinical practice. 2 For example, several studies have explored the relationship between nurses and technology in practice and concluded that the value of The clinical decision support system is utilized to translate knowledge into evidence-based practice in clinical settings.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…9 Over the years, several studies and reviews have been conducted focusing on practitioners' acceptance and use. 2,4,6,10 One study showed that nurses were not overtly influenced by the use of information technology despite its potential to support their clinical practice. 2 For example, several studies have explored the relationship between nurses and technology in practice and concluded that the value of The clinical decision support system is utilized to translate knowledge into evidence-based practice in clinical settings.…”
mentioning
confidence: 97%
“…2,11,12 However, to date, the body of literature on the merits of information technology is scarce and inconsistent. 2,11,12 A recent study reiterated that there is an apparent mismatch between the benefits of CDSS and the adoption of CDSS to support evidence-based decision making, hence not guaranteeing its uptake. 12 As such, it is important to understand the conceptual factors related to its adoption.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nursing researchers have also noticed the importance of exploring human–technology relationships and called for future examinations to explore interactions between nurses and technology, given the increasing volume of technology in nursing workplaces (Henderson ; Lapum et al. ; Moore and Fisher ). For example, in an analysis of nurses using technology for practice, Gough et al.…”
mentioning
confidence: 99%
“…41,42 The Wound CDSS should have increased nurses' autonomy and control in practice, as it is an intelligent, evidence-based, innovative technology developed to support nurses in quality clinical decision making. 1,2 In this study, the Wound CDSS was not entirely seen to provide control and autonomy to practice. Be that as it may, it was uncertain whether there was any ''hidden and unknown'' motive to take the simpler route of trusting peers' decisions rather than seeking evidencebased information.…”
Section: Theme 5: Control Over Nursing Practicesmentioning
confidence: 93%